In-situ construction of high-efficiency phase-transition induced m-Bi2O4/Bi4O7 surface heterojunction photocatalysts and mechanism investigation. (May 2021) - Cheng, Da; Teng, Mengqi; Chen, Yufeng; Wang, Geming; Wang, Shenggao; Yang, Jingjing
Abstract: In this work, pure m-Bi2 O4, Bi4 O7 and m-Bi2 O4 /Bi4 O7 heterojunction photocatalysts with improved visible-light-driven photocatalytic performance have been successfully fabricated by a facile one-pot hydrothermal method. With the prolongation of hydrothermal reaction time, m-Bi2 O4 microrods gradually transform into Bi4 O7 microsheets and m-Bi2 O4 can be in-situ grown on the surface of Bi4 O7, resulting in an intimate interface. The phase structure, morphology, microstructure, surface chemical state and optical property are characterized by X-ray powder diffraction (XRD), Fourier transform-infrared (FT-IR), scanning electron microscopy (SEM), transmission electron microscopy (TEM), UV–visible diffuse reflectance spectroscopy (UV–vis DRS) and X-ray photoelectron spectroscopy (XPS). In comparison with pure m-Bi2 O4 and Bi4 O7, the optimized m-Bi2 O4 /Bi4 O7 composite photocatalysts show higher visible-light-driven photocatalytic performance toward RhB. In view of electronic energy-band structure analysis, photoelectrochemical and photoluminescence spectra (PL) results, we contribute the improved performance to synergetic effects between m-Bi2 O4 and Bi4 O7 in the composite followed a possible S-scheme heterojunction photocatalytic reaction mechanism, which prolongs pathway and suppress the recombination rate of photogenerated carriers. Furthermore, the mechanism of effect of m-Bi2 O4 /Bi4 O7 mass ratio and geometry architecture on photocatalytic behavior is also investigated in this paper. Our work offers a new insight to design and develop high-active phase-transition induced bismuth mixed-valence surface heterojunction photocatalyst with facile preparation. Highlights: A family of m-Bi2 O4 /Bi4 O7 surface heterojunction photocatalysts is facilely synthesized  via one-pot hydrothermal method. The effects of hydrothermal reaction time on the properties of catalysts have been clearly investigated. The optimized m-Bi2 O4 /Bi4 O7  photocatalyst exhibits a high visible-light-driven photocatalytic rate. The photocatalytic performance of m-Bi2 O4 /Bi4 O7 is linked to the synergetic effect between m-Bi2 O4  and Bi4 O7 .